The Transcription Factor Nrf2 Protects Angiogenic Capacity of Endothelial Colony-Forming Cells in High-Oxygen Radical Stress Conditions - Gremmels, Hendrik (Stem Cells Int, 2017)
BACKGROUND: Endothelial colony forming cells (ECFCs) have shown a promise in tissue engineering of vascular constructs, where they act as endothelial progenitor cells. After implantation, ECFCs are likely to be subjected to elevated reactive oxygen species (ROS). The transcription factor Nrf2 regulates the expression of antioxidant enzymes in response to ROS. METHODS: Stable knockdown of Nrf2 and Keap1 was achieved by transduction with lentiviral shRNAs; activation of Nrf2 was induced by incubation with sulforaphane (SFN). Expression of Nrf2 target genes was assessed by qPCR, oxidative stress was assessed using CM-DCFDA, and angiogenesis was quantified by scratch-wound and tubule-formation assays Results. Nrf2 knockdown led to a reduction of antioxidant gene expression and increased ROS. Angiogenesis was disturbed after Nrf2 knockdown even in the absence of ROS. Conversely, angiogenesis was preserved in high ROS conditions after knockdown of Keap1. Preincubation of ECFCs with SFN reduced intracellular ROS in the presence of H(2)O(2) and preserved scratch-wound closure and tubule-formation. RESULTS: Nrf2 knockdown led to a reduction of antioxidant gene expression and increased ROS. Angiogenesis was disturbed after Nrf2 knockdown even in the absence of ROS. Conversely, angiogenesis was preserved in high ROS conditions after knockdown of Keap1. Preincubation of ECFCs with SFN reduced intracellular ROS in the presence of H(2)O(2) and preserved scratch-wound closure and tubule-formation. CONCLUSION: The results of this study indicate that Nrf2 plays an important role in the angiogenic capacity of ECFCs, particularly under conditions of increased oxidative stress. Pretreatment of ECFCs with SFN prior to implantation may be a protective strategy for tissue-engineered constructs or cell therapies.